Development and psychometric evaluation of the Infertility Public Stigma Scale for Japanese women: protocol for an exploratory sequential mixed method study of the Japanese population - Yokota, Rie; Okuhara, Tsuyoshi; Okada, Hiroko; Furukawa, Emi; Shirabe, Ritsuko; Agawa, Toshie; Kato, Hisashi; Kiuchi, Takahiro (Frontiers in Public Health, 2025)
IntroductionWomen undergoing infertility treatment are often tagged with negative labels, subjected to negative reactions and behaviors by laypeople (public stigma), and they internalize these negative values (self-stigma). As self-stigma is associated with poor mental health, a measure is needed to determine the current state of public stigma in Japan and to evaluate the effectiveness of efforts to reduce it. However, existing instruments to measure public stigma in this context are limited. Therefore, this article aims to describe the research protocol for the development of the Infertility Public Stigma Scale for Japanese women and examination of its reliability and validity.Methods and analysisThis study will adopt an exploratory, sequential, mixed-methods design. In the qualitative research phase, the constructs and components of public stigma toward women undergoing infertility treatment will be explored based on interviews with Japanese laypeople. Eligible participants will be recruited through purposive sampling, ensuring maximum variation in sex, age, occupation, place of residence, medical history, and contact with women with primary or secondary infertility. Data will be analyzed using qualitative-descriptive methods and inductive thematic analysis to develop the initial scale. After examining the content validity through an expert panel and cognitive debriefing, laypeople will be surveyed online to test the scale’s validity and reliability. Quantitative research will be conducted using the initial scale. Structural validity will be examined using exploratory and confirmatory factor analyses. Known-groups validity will be tested based on the hypothesis that laypeople aged over 60 years exhibit higher levels of public stigma than younger individuals. Convergent validity will be tested under the hypothesis that individuals with higher levels of fertility knowledge will also report higher levels of public stigma. Convergent and discriminant validity will be examined using a multitrait-scaling analysis. Internal consistency will also be examined by calculating Cronbach’s alpha coefficients and item-total and item-remainder correlations.DiscussionThe development of a reliable and validated public stigma scale for Japanese women undergoing infertility treatment will help understand the current state of public stigma. Simultaneously measuring the effectiveness of intervention studies to reduce public stigma toward women undergoing infertility treatment is also important.